1979
DOI: 10.1002/1097-4679(197907)35:3<576::aid-jclp2270350319>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral correlates of infrequent two-point MMPI code types at a university mental health center

Abstract: Presented interpretive correlates for 95 college students who were seeking mental health services and who generated the following infrequently occurring MMPI code types: Spike 2, 2–0/0–2, 2–4/4–2, 2–6/6–2, 3–4/4–3, 3–9/9–3, 4–7/7–4, 6–7/7–6, 7–9/9–7, and Spike O. Descriptors were derived from intake interview and mental status information collected without knowledge of the MMPI profile. Those items that discriminated between each profile type and the remainder of the student mental health population (Chi Squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…This anger may be the direct result of their tendency to perceive themselves as being "pushed around" by others. The present findings corroborate many of the results of past research on the 4-3 patient (e.g., Dahlstrom et al, 1972;Gilberstadt & Duker, 1965;Kelley & King, 1979).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This anger may be the direct result of their tendency to perceive themselves as being "pushed around" by others. The present findings corroborate many of the results of past research on the 4-3 patient (e.g., Dahlstrom et al, 1972;Gilberstadt & Duker, 1965;Kelley & King, 1979).…”
Section: Discussionsupporting
confidence: 92%
“…Although 12 mental status descriptors differentiated 3-4/4-3 patients from the remainder of the sample, none of the descriptors survived cross-validation. Kelley and King (1979) also reported on the behavioral correlates of 3-4/4-3 high-point pairs in a sample of eight female psychiatric outpatients. Statistically signifi-cant descriptors included musculoskeletal and central nervous system complaints, interpersonal and/or marital problems, excitability, hostile feelings, aggressive outbursts, and sexual problems.…”
mentioning
confidence: 99%
“…Nor were 3-4/4-3 offenders more likely to be incarcerated for violent offenses at the time these data were collected. These findings are consistent with those of previous studies, which failed to verify a violent 4-3 profile code (Buck & Graham, 1978;Gynther et al, 1973;Kelley & King, 1979;Lewandowski & Graham, 1972;Lothstein & Jones, 1978;McCreary, 1976).…”
Section: Discussionsupporting
confidence: 93%
“…This discrepancy between the violence reported in the earlier studies (Davis & Sines, 1971; Persons & Marks, 1971) and the subsequent failures to replicate these findings could be a function of demographic and/or methodological factors. Yet various studies have controlled for the effects of age, sex, and race (Buck & Graham, 1978, Kelley & King, 1979; Lothstein & Jones, 1978; McCreary, 1976); definition of two-point code (Buck & Graham, 1978); and psychiatric or criminal status of subject (Gynther et al, 1973; Lothstein & Jones, 1978; McCreary, 1976). In their study of a medium-security prison population, Buck and Graham (1978) suggested that their failure to find a violent profile for the 4-3 code might have resulted from the more violent prisoners being housed in another facility.…”
Section: Discussionmentioning
confidence: 99%
“…Responses by men in group one ( n = 19) indicated chronic distress and serious psychological problems characterized by emotional instability, anxiety, anger, depression, low self-esteem, dependency, impulsivity, irritability, and interpersonal insensitivity. All 19 cases had scale elevation combinations of 2, 4, 6, 7, and 8 code types that are often associated with borderline personality features (Bell-Pringle, Pate, & Brown, 1997; Kelley & King, 1979; Trull, 1991). The majority of cases had one of the following profile configurations: 8-4-2, 8-2-4, 8-4-7, or 8-2-7 (see Table 1 for specific typology code types).…”
Section: Resultsmentioning
confidence: 99%